Role of women board members in the relationship between internal CSR and firm efficiency: evidence from multiple countries - Setyowati, Arum; Bany-Ariffin, A.N.; Kamarudin, Fakarudin; Matemilola, Bolaji Tunde (Informa UK Limited, 2023)
The study aims to analyze the effect of internal CSR practices on firm efficiency, focusing on the moderating role of women board members. Using a sample set of 5,997 firms from 39 countries between 2008 and 2019, this study performs Data Envelopment Analysis (DEA) to measure firm efficiency and applies a panel regression to investigate the moderation effect of women board members. The empirical results show that women board members play a crucial moderating role in the relationship between internal CSR and firm efficiency. In general, the link between internal CSR and firm efficiency becomes more positive as the proportion of women board members grows. Similar results were reported in the group of developed country. In the developing status group, however, the role of women board members in the positive relationship between internal CSR and firm efficiency was not significant. This study is novel since no prior research has examined the relationship between the presence of women board members in internal CSR-firm efficiency relationships. Moreover, this study employs a broader range of research data, making the conclusions more representative. We recommend investigating additional characteristics of top management, such as experience, education, and age, for future studies.